1996
DOI: 10.4269/ajtmh.1996.54.357
|View full text |Cite
|
Sign up to set email alerts
|

A Polymerase Chain Reaction Assay for Detection of the Parasite Wuchereria bancrofti in Human Blood Samples

Abstract: To identify Wuchereria bancrofti DNA sequences that could be used as the basis for a simple and rapid parasite detection assay, a genomic library of W. bancrofti was constructed and screened for highly repeated DNA. The repeat found with the highest copy number was 195 basepairs (bps) long, 77% AT, and 300 copies per haploid genome. This sequence was designated the Ssp I repeat because it has a unique recognition site for that restriction endonuclease in all or most of the repeat copies. The Ssp I repeat DNA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
8

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 0 publications
0
72
0
8
Order By: Relevance
“…As lâminas foram coradas com hematoxilina pelo método de Carazzi e observadas em microscópio óptico com objetivas e oculares de 10x. 31 ; iv)Controle negativo: soro de amicrofilarêmicos, moradores de área não endêmica. As amostras de soro dos grupos foram aliquotadas (50µl de cada amostra de soro com as mesmas características clínicas) na forma de pool e assim empregadas na realização das reações imunoquímicas (Western-blot, imunofluorescência e dot-blot).…”
Section: Methodsunclassified
“…As lâminas foram coradas com hematoxilina pelo método de Carazzi e observadas em microscópio óptico com objetivas e oculares de 10x. 31 ; iv)Controle negativo: soro de amicrofilarêmicos, moradores de área não endêmica. As amostras de soro dos grupos foram aliquotadas (50µl de cada amostra de soro com as mesmas características clínicas) na forma de pool e assim empregadas na realização das reações imunoquímicas (Western-blot, imunofluorescência e dot-blot).…”
Section: Methodsunclassified
“…A polymerase Chain reaction (PCR) assay based on highly repeated DNA has been developed for the diagnosis of W.bancrofti infection (7). Studies have been shown that this assay is highly sensitive and can even detect single microfilaria in the blood samples from infected individuals.…”
Section: Pcr Based Detection System In Human Lymphatic Filariasismentioning
confidence: 99%
“…This was repeated for 35 cycles, before a further elongation step at 72 o C for ten minutes. The primer pair used in this study, forward 5' CGTGATGGCATAAAGTAGCG 3' and reverse 3' CCTCACTTACCATAAGACAAC 5'), were originally designed by Zhong, et al (9). They amplified 188bp fragment of W. bancrofti DNA sequence.…”
Section: Dna Extraction and Pcr Amplificationmentioning
confidence: 99%